2018
DOI: 10.31234/osf.io/d3nk9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncovering general, shared, and unique temporal patterns in ambulatory assessment data

Abstract: Intensive longitudinal data provide psychological researchers with the potential to better understand individual-level temporal processes. While the collection of such data has become increasingly common, there are a comparatively small number of methods well-suited for analyzing these data, and many methods assume homogeneity across individuals. A recent development rooted in structural equation and vector autoregressive modeling, Subgrouping Group Iterative Multiple Model Estimation (S-GIMME), provides one m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 45 publications
2
49
0
Order By: Relevance
“…First, the sample of participants was relatively small. However, as the time series data used in our analysis had many more observations than time series data previously used to validate the GIMME/uSEM method (60–200 time points, vs. the 950 time points used in the current study; Gates & Molenaar, ; Lane, Gates, Pike, Beltz, & Wright, ), this analysis likely had relatively high power to detect functional connections between ROIs at the individual subject level. As accurate recovery of connections present in a group can be obtained with as few as 10 subjects (Gates & Molenaar, ), we can be reasonably confident that the path counts reported in the group frequency maps closely approximate the true number of connections in the sample.…”
Section: Discussionmentioning
confidence: 99%
“…First, the sample of participants was relatively small. However, as the time series data used in our analysis had many more observations than time series data previously used to validate the GIMME/uSEM method (60–200 time points, vs. the 950 time points used in the current study; Gates & Molenaar, ; Lane, Gates, Pike, Beltz, & Wright, ), this analysis likely had relatively high power to detect functional connections between ROIs at the individual subject level. As accurate recovery of connections present in a group can be obtained with as few as 10 subjects (Gates & Molenaar, ), we can be reasonably confident that the path counts reported in the group frequency maps closely approximate the true number of connections in the sample.…”
Section: Discussionmentioning
confidence: 99%
“…The second subgroup was best described by contemporaneous relationships between anxiety and mood lability and impulsivity, mood lability and urgency and anger, and urgency and emptiness. Interestingly, the third subgroup consisted of just one individual (Lane et al, 2018). Empirical results suggest that GIMME methods can be used for ecological momentary assessment data and provide direction for researchers interested in analyzing and comparing how idiographic and group level models differ from each other within the same sample.…”
Section: Several Studies Have Utilized the Gimme And S-gimme Methods mentioning
confidence: 96%
“…Lane and colleagues used S-GIMME to describe results using daily diary data from a subsample of individuals with borderline personality disorder (i.e., the same sample discussed earlier in Wright et al, 2016). Daily responses regarding mood lability, anxiety, depression, anger, impulsivity, emptiness, and urgency were collected and entered into the S-GIMME model (Lane, Gates, Pike, Beltz, & Wright, 2018). Results suggested that mood lability predicted depression over the course of the day and all items exhibited some stability over time (i.e., statistically significant autoregressive relationships).…”
Section: Several Studies Have Utilized the Gimme And S-gimme Methods mentioning
confidence: 99%
“…These become what are considered the group-level paths. GIMME has previously only been evaluated at the 75% threshold for what defines the "majority" (Gates et al, 2017;Gates & Molenaar, 2012;S. Lane et al, 2018).…”
Section: Data Generationmentioning
confidence: 99%